Cell cycle kinetics, apoptosis rates and gene expressions of MDR-1, TP53, BCL-2 and BAX in transmissible venereal tumour cells and their association with therapy response - Flórez, M. M. [UNESP]; Fêo, H. B. [UNESP]; da Silva, G. N.; Yamatogi, R. S. [UNESP]; Aguiar, A. J. [UNESP]; Araújo, J. P. [UNESP]; Rocha, N. S. [UNESP] (Wiley, 2017)
Transmissible venereal tumour (TVT) generally presents different degrees of aggressiveness, which makes them unresponsive to conventional treatment protocols. This implies a progressive alteration of their biological profile. This study aimed to evaluate the cytotoxicity, cell survival, apoptosis and cell cycle alterations in TVT cell cultures subjected to treatment with vincristine. Similarly, it assessed possible implications of MDR-1, TP53, BCL-2, and BAX gene expressions in eight TVT primary cultures for both resistance to chemotherapy and biological behaviour. When comparing TVT cells receiving vincristine to those untreated, a statistical difference related to increased cytotoxicity and decreased survival rates, and alterations in G1 and S cell cycle phases were found but without detectable differences in apoptosis. Increased MDR-1 gene expression was observed after treatment. The groups did not differ statistically in relation to the TP53, BAX and BCL-2 genes. Although preliminary, the findings suggest that such augmented expression is related to tumour malignancy and chemotherapy resistance.
Keywords: apoptosis; chemotherapy; cytotoxicity; MDR-1; toxicogenomic